Care to adolescents in primary assistance: professionals’ discourse about the focus of comprehensiveness - Maria Veraci Oliveira Queiroz; Nájori Bárbara Ferreira de Lucena; Eysler Gonçalves Maia Brasil; Ilvana Lima Verde Gomes (Rev Rene)
The objective of this research was to analyze the professionals’ discourse on the care to adolescents in primary assistance, identifying the knowledge, actions on the focus of comprehensiveness. It is a qualitative research with assumptions of the Collective Subject Discourse. The interview was carried out with 11 health professionals from Basic Health Units Family of Fortaleza-CE-Brazil. In the analysis, the speeches were grouped into two themes: Perception of care to adolescents in primary assistance. The professionals’ knowledge on the actions of adolescent’s health and comprehensiveness. Professionals considered gaps in the actions and lack of direction of activities for adolescents. They also emphasized that the majority of the teenagers search for the service in situations of health problems, pregnancy and vaccine prevention. It was observed lack of knowledge on the policies for the care to adolescents. Therefore it is necessary to direct actions for this population, including professional training.